PERAN PERSEPSI TERHADAP AI DAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KINERJA UMKM DI ERA DIGITAL - Dwi Novitasari; Fadia Jasmine Has Shiela; Khoirun Nisa; Indah Karimatul Hasanah; Arif Suwarjono (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
This study examines the role of artificial intelligence (AI) adoption and transformational leadership in enhancing the performance of small and medium-sized enterprises (SMEs) in the digital era. SMEs, particularly in Indonesia, face challenges in adopting AI due to factors such as high costs, limited digital skills, and inadequate infrastructure. However, AI has the potential to improve operational efficiency, decision-making, and customer satisfaction. The research explores the interactions between AI perception, transformational leadership, and organizational readiness to change, all of which influence SME performance. The study uses a quantitative approach, employing survey methods with a sample of 144 respondents from SMEs in Surabaya, specifically focusing on the seafood processing industry. The data is analyzed using Structural Equation Modeling (SEM) to test the proposed hypotheses. Findings indicate that a positive perception of AI significantly impacts SME performance, with transformational leadership playing a crucial role in motivating employees to embrace digital innovation. Organizational readiness is identified as a key mediator between AI adoption and performance, highlighting the importance of preparing SMEs for digital transformation. The research contributes to understanding how AI and leadership practices can be integrated into SME operations to foster growth in the digital age. The study provides actionable insights for policymakers, business owners, and managers on fostering a conducive environment for AI adoption and digital transformation.